The Relationship of Breakfast and Nutritional Status of High School Students in Palembang City - Siregar, Afriyana; Hartati, Yuli; Telisa, Imelda; Krisnasary, Arie (jitek, 2024)
This study was conducted in Palembang from June to August 2023, using descriptive analysis methods and a cross-sectional design. The research subjects were high school students from 3 schools, selected using a simple random sampling technique with a sample size of 50 students. Data about breakfast patterns in the form of breakfast habits, energy intake, and breakfast macronutrients were collected using questionnaires and 3 x 24-hour recall forms. Nutritional status was measured by measuring body weight and height to find nutritional status based on BMI/U and categorized based on the Minister of Health's Regulation on Children's Anthropometric Standards 2020. Data were analyzed using the chi-square statistical test. The research results showed that almost half of the students' breakfast energy intake was in the normal category (48%). Nearly half of the students' breakfast protein intake was in the more category (42%). Almost half of the students' breakfast fat intake was in the normal category (48%). Most students' breakfast carbohydrate intake was deficient (52%), and most students' nutritional status was normal (60%). A relationship exists between energy and fat intake at breakfast and students' nutritional status. Although protein and carbohydrate intake varies, this research provides critical insight into the factors that influence the well-being of high school students. Suggestions from this research can be used as a reference for developing more efficient nutrition intervention programs in schools to improve the health and welfare of adolescent students.